Comparative FISH-Mapping of MC1R, ASIP, and TYRP1 in New and Old World Camelids and Association Analysis With Coat Color Phenotypes in the Dromedary (Camelus dromedarius) - Alshanbari, Fahad; Castaneda, Caitlin; Juras, Rytis; Hillhouse, Andrew; Mendoza, Mayra N.; Gutiérrez, Gustavo A.; Ponce de León, Federico Abel; Raudsepp, Terje (Frontiers in Genetics, 2019)
Melanocortin 1 receptor (MC1R), the agouti signaling protein (ASIP) and tyrosinase related protein 1 (TYRP1) are among the major regulators of pigmentation in mammals. Recently, MC1R and ASIP sequence variants were associated with white and black/dark brown coat colors, respectively, in the dromedary. Here we confirmed this association by independent sequencing and mutation discovery of MC1R and ASIP coding regions and by TaqMan genotyping in 188 dromedaries from Saudi Arabia and United States, including 38 black, 53 white and 97 beige/brown/red animals. We showed that heterozygosity for a missense mutation c.901C>T in MC1R is sufficient for the white coat color suggesting a possible dominant negative effect. Likewise, we confirmed that the majority of black dromedaries were homozygous for a frameshift mutation in ASIP exon 2, except for 4 animals, which were heterozygous. In search for additional mutations underlying the black color, we identified another frameshift mutation in ASIP exon 4 and 6 new variants in MC1R including a significantly associated SNP in 3’UTR . In pursuit of sequence variants that may modify dromedary wild-type color from dark-reddish brown to light beige, we identified 4 SNPs and one insertion in TYRP1 noncoding regions. However, none of these were associated with variations in wild-type colors. Finally, the three genes were cytogenetically mapped in New World (alpaca) and Old World (dromedary and Bactrian camel) camelids. The MC1R was assigned to chr21, ASIP to chr19 and TYRP1 to chr4 in all 3 species confirming extensive conservation of camelid karyotypes. Notably, while the locations of ASIP and TYRP1 were in agreement with human-camelid comparative map, mapping MC1R identified a new evolutionary conserved synteny segment between camelid chromosome 21 and HSA16. The findings contribute to coat color genomics and the development of molecular tests in camelids and towards the chromosome level reference assemblies of camelid genomes.